RELATIONAL CONCEPT OF MA’RIFAH, ‘ILM, AND WAHY: : A Semantic Analysis of Islamic Studies in the Qur’an - Ismail, Moh; Awaluddin Faj; Aat Mupliah (Jurnal Al I'jaz, 2024)
The concepts of ma’rifah, 'ilm, and wahy in Islamic ideology are crucial for comprehensively understanding knowledge and spiritual development in Islam. However, recently, there has often been confusion in distinguishing these key concepts in Islam, such as the concept of knowledge, which should bring one closer to Allah Swt. but instead distances one from religious values. This research aims to elucidate these relational notions through qualitative semantic analysis, providing clarity and depth to their interconnections and individual significance. The urgency of this study lies in the necessity to precisely differentiate Islamic ideology from Islamic education to enhance the accuracy and effectiveness of educational curricula. By employing a qualitative method for semantic analysis of the Qur'anic verses, this research delves into the profound meanings and implications of ma’rifah, 'ilm, and wahy. The key findings reveal that ma’rifah emphasizes a deeper understanding and consciousness of divine truths, while 'ilm encompasses both religious, encouraging continuous learning and intellectual inquiry. Wahy, on the other hand, serves as the ultimate source of guidance and wisdom, steering believers towards ethical conduct and spiritual enlightenment. The analysis of specific Qur'anic verses related to spiritual practices, intellectual growth, and moral guidance illustrates the interconnectedness of these elements within the Islamic worldview. The research offers significant implications for educational environments, moral development, and character building. Future studies could explore practical applications of these concepts in educational curricula and strategies for fostering comprehensive development rooted in Islamic values. Understanding these principles is crucial for nurturing a profound connection with the divine, promoting mindfulness, appreciation, and spiritual awareness among adherents, and leading lives that are ethically and purposefully aligned with the teachings of the Qur’an.